Changes in insulin sensitivity and secretion after sleeve gastrectomy. Issue 3 (9th November 2015) - Casella, G.; Soricelli, E.; Castagneto‐Gissey, L.; Redler, A.; Basso, N.; Mingrone, G.
Abstract: Background: Sleeve gastrectomy is indicated for the treatment of obesity and related co‐morbidity including diabetes. The dynamic changes in insulin secretion and sensitivity after sleeve gastrectomy are unknown. Methods: Whole‐body insulin sensitivity was measured by the euglycaemic hyperinsulinaemic clamp technique, and insulin secretion by C‐peptide deconvolution after an oral glucose tolerance test (OGTT), before and 3, 6 and 12 months after sleeve gastrectomy in morbidly obese subjects. The time course of glucagon‐like peptide (GLP) 1, as a marker of insulin secretion following OGTT, was also assessed. Results: Ten patients were included in the study. Median (range) baseline insulin sensitivity (M‐value) increased from 84·0 (20·2–131·4) mmol per kg per min at baseline to 122·8 (99·0–179·3) mmol per kg per min at 12 months after surgery ( P = 0·015). Fasting insulin sensitivity, measured by homeostatic model assessment of insulin resistance, which represents a surrogate index of hepatic insulin resistance, decreased from 3·3 (1·9–5·5) to 0·7 (0·5–1·1) mg/dl·µunits/ml ( P < 0·001). Total insulin secretion, measured as incremental area under the curve (AUC), after OGTT decreased from 360·4 (347·9–548·0) to 190·1 (10·1–252·0) mmol/l·180 min at 12 months ( P = 0·011). The AUC for GLP‐1 increased from 258·5 (97·5–552·6) to 5531·8 (4143·0–7540·9) pmol/l·180 min at 12 months after sleeve gastrectomy ( P < 0·001). In multiple regression analysis, 51 per cent of the M‐value variability was explained by GLP‐1 secretion. Conclusion: Sleeve gastrectomy improved insulin sensitivity and reduced insulin secretion within 6 months after surgery. Although there was a correlation between insulin sensitivity and bodyweight, the major driver of the improvement in insulin sensitivity was GLP‐1 secretion. Abstract : Improves insulin sensitivity, reduces insulin secretion